When do predatory mites (Phytoseiidae) attack? Understanding their diel and seasonal predation patterns. (11th August 2017) - Pérez‐Sayas, Consuelo; Aguilar‐Fenollosa, Ernestina; Hurtado, Mónica A.; Jaques, Josep A.; Pina, Tatiana
Abstract: Predatory mites of the Phytoseiidae family are considered one of the most important groups of natural enemies used in biological control. The behavioral patterns of arthropods can differ greatly daily and seasonally; however, there is a lack of literature related to Phytoseiidae diel and seasonal predation patterns. The predatory activity of three phytoseiid species (two Tetranychidae‐specialists, Phytoseiulus persimilis and Neoseiulus californicus, and one omnivore, Euseius stipulatus ) that occur naturally in Spanish citrus orchards was observed under laboratory conditions in winter and summer. The temperature and photoperiod of the climatic chamber where the mites were reared did not change during the experiment. Our study demonstrates that phytoseiids can exhibit diel and seasonal predatory patterns when feeding on Tetranychus urticae (Acari: Tetranychidae). Neoseiulus californicus was revealed to be a nocturnal predator in summer but diurnal in winter. In contrast, P. persimilis activity was maximal during the daytime, and E. stipulatus showed no clear daily predation patterns. The predatory patterns described in this study should be taken into account when designing laboratory studies and also in field samplings, especially when applying molecular techniques to unveil trophic relationships.